If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = 2y + -3 + -3y Reorder the terms: -7 = -3 + 2y + -3y Combine like terms: 2y + -3y = -1y -7 = -3 + -1y Solving -7 = -3 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -7 + y = -3 + -1y + y Combine like terms: -1y + y = 0 -7 + y = -3 + 0 -7 + y = -3 Add '7' to each side of the equation. -7 + 7 + y = -3 + 7 Combine like terms: -7 + 7 = 0 0 + y = -3 + 7 y = -3 + 7 Combine like terms: -3 + 7 = 4 y = 4 Simplifying y = 4
| 3x-7(-2x+8)=-5 | | 3x-7y=-5 | | 10n+8p=0 | | S=3t+40 | | (x-1)+(x+3)=2x | | k-8(7+k)=-1(5) | | 4t-3-3t=-5 | | 9x+3y=4 | | (3x+4)(2-5x)=0 | | c=(2)(3.14)(r) | | 9x-4y=-2 | | 6.3y=4.1y+12 | | 1.2=1.6m | | c=23 | | -8=5a-3a | | -54=133.578499968x+0.5*0.0209625668*17843.21565 | | 6(x+2)-(3x-8)= | | 4(x+3)-(2x-4)= | | 54=133.578499968x+0.5*0.0209625668*17843.21565 | | 3b+(4b-6b+2)-b=10 | | 13t^2-10t+2=0 | | 11t-8t=-3 | | 11=x-(-9) | | 7*x-2=0 | | x(2)+3=x | | -9(12)*15(145)+4b=3 | | 4m-8n-7m=0 | | a-10=-16 | | 5z-3=17 | | 7a^2-64a+64=0 | | x^2=7.84+2*0.0209625668*133 | | 0=ln(x-5) |